Akselerasi Kapasitas Masyarakat Melalui Pelatihan dan Inovasi Digital di Desa Ciparigi - Mohamad Fazar Fadilah; Aldi Syahrul Mauladi; Zulfiati Khoeriyah; Rima Nurmala; Clara Pramudita; Aura Qeyshadida; Yunita Choirunnisa; Nova Syaidah Laila; Muhammad Randi Adhari; Ai Nuryani; Dian Aulia Hayati; Hana Siti Robiatu S; Muhammad Irfan Asyidiq; Mochammad Lipaldi; Linda Melinda; Mysha Aisa Nurfika (Universitas Perjuangan Tasikmalaya, 2026)
This community empowerment program through a 35-day service-learning KKN in Ciparigi Village, Sukadana, Ciamis, aimed to strengthen human capital, improve public services, and revitalize local microenterprises, especially honey producers and handicrafts. The team applied participatory observation, focus group discussions, and issue–potential mapping to co-design six workstreams: education, health, economy, environment, institutional strengthening, and disaster mitigation. Key outputs included: interactive teaching and recycling crafts in elementary schools, nutrition and anti-stunting outreach, aloe-based hand sanitizer practice, digital marketing mentoring for UMKM and halal certification socialization, a village gate and waste bins, a web-based asset inventory, and tree planting in landslide-prone areas. Quantitatively, 11 programs engaged around 200 beneficiaries; qualitatively, motivation to learn rose, hygiene and nutrition awareness improved, UMKM began online promotion, and village administration became more efficient. The program demonstrates an integrated model linking livelihood upgrading, civic infrastructure, and digital public goods for sustainable community capacity building.